Comportamiento agronómico del cultivo de pepino (cucumis sativus. l). Con diferentes abonos orgánicos en el colegio Pueblo Nuevo canton El Empalme, año 2014 - Villavicencio Vivas, Galo Mauricio (2015)
The agronomic performance of crop cucumber (Cucumis sativus. L) research with different organic fertilizers developed in Pueblo Nuevo College, parish El Guayas, Canton El Empalme. Whose geographical location is 1 ° 59' 25' south latitude and 79 ° 34' 19' west longitude. The trial lasted 120 days and different doses d manure was evaluated. The Design of Randomized Complete Block (RCBD) with seven treatments and four replicates per treatment was used. To determine the statistical difference test Tukey multiple range up to 95% was used; the experimental unit consisted of twenty plants. When calculating the variable plant height significant differences seen in the different days of assessment, most plant height at 15, 30, 45 and 60 days was obtained by treatment with 5kg of Dunger 14.30; 77.45; 158.00 and 202.09 in your order. The treatment showed better results on flowering were humus Dunger 5kg and 1kg. The more premature harvest treatment was the humus 5kg the treatment was the best performer in the number of fruits per plant was humus 5kg. With the amount of 6.29. The lowest results obtained them without fertilizer treatment with average length of 19.51 and treatments were expressed higher result, Dunger 5kg an average length of 25.39 and humus 5kg with a 25.09 average length of the other treatments showed no significant difference. Fruit diameter showed no significant differences between the treatments tested. Treatment which showed the best 5 kg weight was Dunger weighing 468.16. In Table 16 we note that the higher total cost had the treatement Dunger 5kg. With $ 69.56 and the lowest cost is obtained treatment without fertilizer with $ 33.00El which showed the highest gross income was Humus 5kg treatment. With $ 101.80 and daring the lower income was the treatment without fertilizer with a value of $ 79.80El greatest net benefit threw him treatment without fertilizer with a value of $ 46.80 and it has the lowest was treatment Dunger 5kg with a value of $ 22.84.